2000
DOI: 10.1128/aac.44.3.602-607.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antimembrane Activities of Cecropin A in Escherichia coli

Abstract: The ability of cecropin A to permeabilize and depolarize the membranes of Escherichia coli ML-35p bacteria has been compared to its bactericidal activity in an extension of earlier studies performed on synthetic lipid vesicle membranes (L. Silvestro, K. Gupta, J. H. Weiser, and P. H. Axelsen, Biochemistry 36:11452-11460, 1997). Our results indicate that differences in the concentration dependences of membrane permeabilization and depolarization seen in synthetic vesicles are not manifested in whole bacteria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 26 publications
6
100
0
1
Order By: Relevance
“…On the other hand, the seeds may also act directly upon microorganisms and result in growth inhibition. Antimicrobial peptides are thought to act by disrupting the cell membrane or by inhibiting essential enzymes (Silvestro et al, 2000;Suarez et al, 2003). Sutherland et al (1990) reported that Moringa seeds could inhibit the replication of bacteriophages.…”
Section: Microbial Elimination With Moringa Seedsmentioning
confidence: 99%
“…On the other hand, the seeds may also act directly upon microorganisms and result in growth inhibition. Antimicrobial peptides are thought to act by disrupting the cell membrane or by inhibiting essential enzymes (Silvestro et al, 2000;Suarez et al, 2003). Sutherland et al (1990) reported that Moringa seeds could inhibit the replication of bacteriophages.…”
Section: Microbial Elimination With Moringa Seedsmentioning
confidence: 99%
“…Antimicrobial peptides clearly have an affinity for membranes and exert an array of membrane-invasive activities, including folding-insertion reactions (19), channel formation (4), pore formation (21), and complete structural disruption (18). However, there are virtually no reliable data indicating that anionic lipids are present on the extracellular surface of the bacterial cell membrane, and several important structure-activity relationships are not adequately explained by this mechanism.…”
mentioning
confidence: 99%
“…The pore-forming peptides discovered by screening the β-hairpin library in lipid vesicles thus share features in common with naturallyoccurring, pore-forming antimicrobial peptides (AMP) (27). We hypothesized that the mechanism of pore-formation in biological membranes is also similar, however, the correlation between structure and function of pore-forming peptide in vesicles and in biological membranes remains controversial (28). Therefore, we characterized the antimicrobial and cytotoxic activity of four similar peptides originating from this framework that have very different structures and pore-forming propensities in vesicles, including members of the library that do not form pores in vesicles under stringent conditions.…”
mentioning
confidence: 99%